Digital media, projection design, and technology for theatre - Oliszewski, Alex; Fine, Daniel; Roth, Daniel (Media Designer) (Routledge, 2018)
"Digital Media, Projection Design, and Technology for Theatre covers the foundational skills, best practices, and real-world considerations of integrating digital media and projections into theatre. The authors, professional designers and university professors of digital media in live performance, provide readers with a narrative overview of the professional field, including current industry standards and expectations for digital media/projection design, its related technologies and techniques. The book offers a practical taxonomy of what digital media is and how we create meaning through its use on the theatrical stage. The book outlines the digital media/projection designer's workflow into nine unique phases. From the very first steps of landing the job, to reading and analyzing the script and creating content, all the way through to opening night and archiving a design. Detailed analysis, tips, case studies and best practices for crafting a practical schedule and budget, to rehearsing with digital media, working with actors and directors, to creating a unified design for the stage with lighting, set, sound, costumes, and props is discussed. A companion website offers an interactive timeline of the history and important milestones in projection design, sample assets, and interviews that link to current and relevant work of leading projection designers" --